Microfinance Position and Indebtedness: Empirical Evidence from Microfinance Institutions in Nepa - Risal, Nischal (Pravaha, 2018)
The paper has been built up with the aim of analyzing the microfinance institutions status and indebtedness in Nepal. Initially, the paper starts with the thematic review based on etymological, ontological, epistemological dimensions then the status of microfinance institutions and indebtedness in Nepal have been presented in the second part. The descriptive analytical research design has been adopted to analyze and interpret the population data. The fifty three microfinance institutions' data have been reviewed, tabulated and analyzed using MSExcel. The microfinance institutions have been found efficient in saving and credit services. The microfinance credit service has not been utilized as per the need of the people and capacity of the institutions. The loan recovery, interest recovery, clients awareness/activeness have been found effective. Overall, microfinance institutions status has been found sound. Only few institutions are below the satisfaction level. The microfinance services in terms of micro loan are not uniform among microfinance institutions. The indebtedness challenge have found at bottom level in the microfinance industry. It is recommended to all the microfinance institutions to come up with policies, strategies and regulatory framework to benchmark the level of tolerance to indebtedness, so that the microfinance institutions may sustain by achieving the objectives of poverty alleviation through microfinance services. Pravaha Vol. 24, No. 1, 2018, Page: 120-136